The quest for 'newness' in jazz: implications of Cage's relationship with jazz - Chan, Cheong Jan (Universiti Pendidikan Sultan Idris, 2013)
Scott Simon (2008) describes jazz improvisation as an act of ‘reproduction of music’, ‘reinterpretation of compositions’, and ‘quotations of melodies’, while Paul Berliner (1994) puts it as ‘reworking precomposed material’. In contrast, Lee Brown highlights the spirit of ‘non conformism’ embedded in jazz playing, so that the musical outcome of jazz is ‘unanticipated’, and ‘nondeterministic’ (Brown, 2000). In 2012, I proposed ‘heteronomy’ as one of the defining features of jazz. How would these characters of jazz appear in the light of John Cage’s thoughts? If jazz is an art of quoting rather than creating, then that it was a genre of ‘distaste’ to Cage becomes understandable. Cage’s relationship to jazz and/or improvisation is more than a mild rejection. Sabine Feisst (2009) refers to it as an ‘unresolved relationship’, while for Rebecca Kim (2012) there is a ‘separate togetherness’ between Cage and jazz. In coaching Malaysian students to embrace jazz, needs arise for a clear understanding of what is the nature of jazz. In this paper, I discuss the meaning of ‘newness’ in jazz, by tracing several issues that crisscross over Cage’s thoughts about jazz. Do musicians seek ‘newness’ in jazz? I argue that ‘newness’ is more relevant in the process of a jazz performance compared to its outcome. Nevertheless, Cage’s thoughts could inspire further pondering of what jazz is (not), and what jazz can (not) become.